Mitotic activity of anti-histone H1 sIgA-antibodies from milk of healthy mothers - Starykovych, M.O.; Stoika, R.S.; Kit, Yu.Ya. (Вiopolymers and Cell, 2013)
Aim. Earlier, we have shown that antibody (AT) preparations obtained by precipitation with 50 % ammonium sulfate from milk of some healthy mothers possess pro-proliferative activity toward transformed and tumor cells in vitro (Kit et al., 2008). We hypothesized that this effect is associated with the presence of the anti-histone H1 sIgAs in AT preparations. Methods. To check this hypothesis, we obtained electrophore- tically homogeneous anti-histone H1 sIgAs from milk of healthy mothers by sequential chromatography on protein A-Agarose, protein G- Sepharose and histone H1-Sepharose respectively. These Ab were tested on a proliferative activity toward human T-leukemia Jurkat and human melanoma SK-MEL cells. Results. It was found that anti-histone H1 sIgAs are able to stimulate proliferation of both tumor cell lines. Mitotic effect of these AB was confirmed with an increase of signal proteins involved in cell proliferation (c-Myc, MAP-and cdc2-protein kinases), detected by Western-blot analysis. We also studied the antigenic reactivity of anti-histone H1 sIgAs toward SK-MEL cell proteins. It was observed that these AB possessed an affinity for a number of melanoma cell proteins with molecular masses of 60, 55, 48 and 38 kDa. Conclusions. It has been found that anti-histone H1 sIgA antibodies can stimulate proliferation of human T-leukemia Jurkat and human melanoma SK-MEL cells in vitro. The cross reactivity of these AB could serve as an explanation of their mitotic activity toward the target cells.